The Effectiveness of Transcutaneous Electrical Nerve Stimulation (TENS) For Reducing Pain in Burn Patients: Literature Review - Lestari, Siska Tri; Sari, Putri Irwanti; Sari, Fasya Puspa Embun; Mutmainnah, Muthia; Lestari, Maya; Oktaria, Rina; Yusnilawati, Yusnilawati; Mawarti, Indah; Sianturi, Gabriela Pricilia; Afrida, Dwi Afrida; Martawinarti, RTS Netisa; Andini, Febri Tri (Jurnal Pinang Masak, 2025)
Transcutaneous Electrical Nerve Stimulation (TENS) is a non-pharmacological therapy method used to reduce pain, including in burn patients. Burns cause complex pain, both acute and chronic, thus requiring multidisciplinary management. This study is a literature review aimed at evaluating the effectiveness of Transcutaneous Electrical Nerve Stimulation (TENS) in reducing pain in burn patients. Data were collected from 10 scientific articles published within the last ten years, including clinical studies, pilot studies, and meta-analyses. The review findings indicate that Transcutaneous Electrical Nerve Stimulation (TENS) is effective in reducing pain intensity, accelerating wound healing, improving sleep quality, and decreasing the need for pharmacological analgesics. Additionally, the use of Transcutaneous Electrical Nerve Stimulation (TENS) has been reported as safe and does not cause significant side effects. However, most of the analyzed studies still have limitations, such as small sample sizes and short intervention durations. Therefore, further research with stronger experimental designs is needed to strengthen clinical evidence and support the implementation of Transcutaneous Electrical Nerve Stimulation (TENS) as part of pain management in burn patients.